Structural and energetic basis of isopropylmalate dehydrogenase enzyme catalysis. (4th October 2014) - Palló, Anna; Oláh, Julianna; Gráczer, Éva; Merli, Angelo; Závodszky, Péter; Weiss, Manfred S.; Vas, Mária
<x xml:space="preserve">Abstract</x> The three‐dimensional structure of the enzyme 3‐isopropylmalate dehydrogenase from the bacterium Thermus thermophilus in complex with Mn2+, its substrate isopropylmalate and its co‐factor product NADH at 2.0 Å resolution features a fully closed conformation of the enzyme. Upon closure of the two domains, the substrate and the co‐factor are brought into precise relative orientation and close proximity, with a distance between the C2 atom of the substrate and the C4N atom of the pyridine ring of the co‐factor of approximately 3.0 Å. The structure further shows binding of a K+ ion close to the active site, and provides an explanation for its known activating effect. Hence, this structure is an excellent mimic for the enzymatically competent complex. Using high‐level QM/MM calculations, it may be demonstrated that, in the observed arrangement of the reactants, transfer of a hydride from the C2 atom of 3‐isopropylmalate to the C4N atom of the pyridine ring of NAD+ is easily possible, with an activation energy of approximately 15 kcal·mol−1. The activation energy increases by approximately 4–6 kcal·mol−1 when the K+ ion is omitted from the calculations. In the most plausible scenario, prior to hydride transfer the ε‐amino group of Lys185 acts as a general base in the reaction, aiding the deprotonation reaction of 3‐isopropylmalate prior to hydride transfer by employing a low‐barrier proton shuttle mechanism involving a water molecule. Database Structural data have been submitted to the Protein Data Bank under accession number 4F7I.